Perlindungan Hukum Terhadap Kreditur Pemegang Hak Tanggungan Atas Upaya Pihak Ketiga Untuk Meletakan Sita - Sahal Afhami (Scholar Center, 2021)
Banking institutions as a financial institution operate and collect fundsfrom the public in the form of deposits and distribute them to the public in the form of credit or other forms, of course, are closely related to the risks that occur. The main risk in providing credit is bad credit. Given this risk, banks in providing credit are not only based on binding credit agreements, but often also require accessor agreements in the form of material guarantees. The material agreement that is often required in the granting of credit in large amounts is the binding of mortgage rights on land and or buildings. However, in fact, even though the mortgage has been installed at the time of bad credit, there is often resistance from the debtor or the owner of the guarantee and even a third party that the debtor has planned so that a confiscation can be placed on an object that has been encumbered with a mortgage in order to hinder or stop the execution. The problems that we raise are how legal protection is and how efforts can be made if there is resistance or attempts to place confiscations on mortgage objects to interfere with the auction. The type of legal research used is doctrinal research, with a statutory, conceptual, and comparative approach. From the research, it was found that the provisions of Law Number 4 of 1996 concerning Mortgage Rights and other provisions have provided legal protection to mortgage holders for efforts to place confiscations, in addition creditors holding mortgages can also intervene or file resistance claims in case between the owner of the collateral and a third party requesting the placement of the confiscation.